Sub-National Spending in Timor-Leste : Lessons from Experience - World Bank (Washington, DC, 2014)
This Policy Note distils the findings and recommendations of a Study, jointly undertaken by the World Bank and the Government of Timor-Leste, that evaluates the mechanisms used by the Government to manage sub-national spending in recent years: i) the Local Development Program (Programa Dezenvolvimentu Lokal, PDL), underway since 2004; and ii) the Referendum Package (Pakote Referendum, PR), initiated in 2009, and progressively refined as the Decentralized Development Program (Programa de Dezenvolvimentu Desentralizadu, PDD) since 2010. The Study assesses how these programs have performed in respect of a number of key government policy priorities and draws conclusions and lessons for the future. It adopts a dynamic approach, so as to adequately acknowledge and account for how shifts in the government s policy priorities over time, in response to the changing context, were reflected in the institutional arrangements that govern sub-national spending.